Adherence to Treatment in Diabetic Patients in Lebanon - Yassin, Nour (Technium Social Sciences Journal, 2022)
Non-adherence to prescribed treatment represents an important dilemma that deserves special attention especially when dealing with chronic and critical diseases as in diabetes mellitus. The objective of this study was to evaluate the level of adherence in Lebanese adult outpatients suffering from diabetes mellitus, where they may present other illness and to identify the possible predictors of non-adherence in this patient group.A questionnaire was administered face-to-face to a sample of Lebanese adults visiting two pharmacies and two endocrinologist clinics. The questionnaire covered the socio-demographics, lifestyle and health status of the patients, regimen characteristics, drug affordability, relationship with healthcare provider, and patients’ attitudes and beliefs. The level of adherence was assessed using the 8-item Morisky Medication Adherence Scale. Statistical analysis was performed using SPSS version 17. Univariate associations between drug adherence and patient and drugs characteristics were tested using chi-square test. Out of the 130 patients included in this study, 64.6% were classified as adherent and 35.4% were not. In the univariate analyses, statistically significant predictors of low adherence included smoking status(p=0.012) , level of stress and anxiety (p=0.009), monthly cost in LL (p=0.049), changing treatment plan a lot recently (p=0.010), taking any acute drugs (p=0.014), forgetting to take their pills (p<0.001), taking their medicine over the past two weeks (p<0.001), cutting back or stop taking their medication without telling their doctor because they felt worse when they took it (p<0.001), forgetting to bring along their medications during traveling (p<0.001), stop taking their medicine when they feel that the disease is under control (p<0.001),feeling disturbed taking medication everyday (p<0.001), difficulty remembering to take all their medications (p<0.001).As forgetfulness being the most important reason of patient non adherence, there should be a cooperative work between healthcare providers in order to overcome such a problem where they should create methods that help in educating patients and improving their adherence.